The effect of implementing corporate governance studies on manufacturing companies listed on the IDX in the 2008 period on disclosure of social responsibility - Larisa Rahman (Institute of Accounting Research and Novation (IARN), 2021)
The objectives of this research observed the influence of corporate governance implementation on corporate social responsibility disclosure. Management ownership, independent board of commissioners, audit committee, and external auditors are used as proxies for corporate governance, with firm size and leverage as control variables. Corporate social responsibility disclosure as a dependent variable. The population in this study is 138 manufacturer companies, which are listed at Indonesian Stock Exchange in 2008 based on Indonesia Capital Market Directory, such us basic industry & chemicals, miscellaneous industry, and consumer goods industry. The sample was taken using the method of purposive sampling and those meeting the selection criteria were also taken. The criteria are listed companies at the Indonesian Stock Exchange in 2008 whose annual reports disclose CSR activities and can access at the Capital Market Reference Center (CMRC). The sample used was from 84 manufacturer companies. This study observed three categories of corporate social responsibility disclosure items from Hackston & Milne (2006) research. These categories are environment, product, and linkage in community. The results indicate that only an external and firm size auditor has a significant positive influence on the disclosure of corporate social responsibility. On the other hand, the percentage of management ownership, the proportion of independent commissioners, audit committees, and leverage failed to show its significant effect.